Influence of Reinforcing Bar Type On Flexural Behavior of R-UHPFRC. (2017) - Kakuma, Ko; Nishi, Hiroaki; Matsumoto, Takashi; Imai, Takashi
Abstract: This study conducted two tests on UHPFRC containing reinforcing bars (R-UHPFRC): a pullout test of reinforcing bars embedded in UHPFRC, and a flexural test. Both tests used deformed bars and round bars, and the pullout and flexural behaviors are discussed, with a focus on the differences associated with the type of reinforcing bar used. Furthermore, the influence of bond characteristics on the flexure of R-UHPFRC was examined by parametric analysis. The results showed that bond-slip behavior between the reinforcing bar and the UHPFRC is influenced by the reinforcing bar type and that the influence of bond characteristics appeared in the post-peak behavior of R-UHPFRC under flexure.